Improving Learning Outcomes of Class 5C Students in Mathematics Learning Using MATLAK Media (Mathemat-ics Through Congklak) at State Elementary School 067240 Medan Tembung (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the use of MATLAK (Mathematics Through Congklak) media in improving mathematics learning for class 5C students at SDN 067240 Medan Tembung. The objectives are to: (1) describe the application of MATLAK in the classroom, (2) determine its impact on students' mathematics learning outcomes, (3) analyze its effect on student motivation and engagement, and (4) assess the effectiveness of the traditional congklak game as a learning tool. Conducted as Classroom Action Research (CAR), this study aims to address classroom learning challenges through reflective cycles that enhance both teaching processes and student outcomes. The findings reveal that the integration of the Problem-Based Learning (PBL) model with MATLAK media, rooted in constructivist principles, significantly increased student activity and understanding, especially when problems presented were closely related to daily life. Students were encouraged to collaborate, think critically, and articulate their ideas during discussions. Additionally, student responses toward the use of MATLAK media were overwhelmingly positive, demonstrating increased motivation and active participation. Teacher observations also showed improvement in classroom engagement and implementation effectiveness from cycle I to cycle II. Overall, the study concludes that using the traditional congklak game as a mathematics learning medium when combined with the PBL model effectively enhances learning outcomes and student involvement in class 5C.